Management of pneumothorax in mechanically ventilated COVID-19 patients: early experience. (31st August 2020) - Hussain, Azhar; Noorani, Alia; Deshpande, Ranjit; John, Lindsay; Baghai, Max; Wendler, Olaf; Whitaker, Donald; Khan, Habib
Abstract: A significant proportion of patients infected with the novel coronavirus, now termed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), require intensive care admission and subsequent mechanical ventilation. Pneumothorax, a potential fatal complication of mechanical ventilation, can further complicate the management of COVID-19 patients, whilst chest drain insertion may increase the risk of transmission of attending staff. We present a case series and a suggested best-practice protocol for how to manage and treat pneumothoraces in COVID-19 patients in an intensive care unit setting. Abstract : The novel coronavirus, now termed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has caused a significant global impact in the space of 4 months.